A new species of Temple Pitviper (Tropidolaemus Wagler, 1830) from Sulawesi, Indonesia (Squamata: Viperidae: Crotalinae) - Kuch, Ulrich; Gumprecht, Andreas; Melaun, Christian (Zootaxa, 2007)
The Asian Temple Pitviper Tropidolaemus wagleri is a widespread polytypic species complex with a complicated taxonomic history, a lengthy species synonymy list, and a geographic distribution encompassing Vietnam, Thailand, Malaysia, Singapore, Brunei, portions of Indonesia, and the Philippines. As a prelude to a comprehensive review of this species complex, we describe a new species of Temple Pitviper based on five historic museum specimens from the Indonesian island of Sulawesi. The new species can be distinguished from sympatric members of the Tropidolaemus subannulatus complex and other congeners on the basis of its conspicuous color pattern and scalation characters. Available collecting data suggest that the new species has a wide distribution in rainforests and lower montane wet forests of Sulawesi Utara and Sulawesi Tengah provinces.